When Brands Complement Patents in Securing the Returns from Technological Innovation: The Case of Bayer Aspirin - Jennewein, Klaus; Durand, Thomas; Gerybadze, Alexander (Management international / Gestiòn Internacional / International Management)

(untitled) (HEC Montréal et Université Paris Dauphine, 2010)
This paper deals with brand equity as a way to complement patents and other technological assets in technology intensive industries. The longitudinal case of Bayer Aspirin is presented. The discussion suggests that while Hi-tech start-ups build a competitive advantage through technology, they can also use this early period to build significant brand equity at limited marketing costs. In turn this brand equity may become increasingly important as the technology life-cycle unfolds. When the next technological revolution strikes, brands may serve as a shield to help the now well-established firms survive through the change.